2002
DOI: 10.1002/1521-4141(200212)32:12<3506::aid-immu3506>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐homing CLA+T cells and regulatory CD25+T cells represent major subsets of human peripheral blood memory T cells migrating in response to CCL1/I‐309

Abstract: Functionally distinct T cell subsets exhibit specific chemokine receptor profiles that regulate their tissue localization. Here, we show that human peripheral blood CD4+ and CD8+ cutaneous (CLA+), but not intestinal memory (integrin β7+) nor IL‐4‐producing T cells, represent major subpopulations of circulating T cells that specifically migrate in response to the chemokine I‐309/CCL1 by virtue of CCR8 expression. Expression of CCR8 is markedly up‐regulated upon activation and in vitro culture of human CLA+ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 37 publications
5
61
0
Order By: Relevance
“…by use of the marker a E (CD103), into a lineage or differentiation stage of natural, naive-like a E -CD25 + Treg and into that of a E + Treg (either CD25 + or CD25 -) with the phenotype of effector/memory cells [3], a distinction that might partially relate to the differentiation into natural and adaptive Treg [4]. Whereas naive-like Treg express molecules including CD62L and CC chemokine receptor 7 (CCR7), allowing recirculation through lymphoid tissues [3,5,6], effector/memory-like Treg display a high chemokine and homing receptor versatility and efficiently migrate into peripheral tissues and inflamed sites [3,5,[7][8][9][10][11][12]. These findings prompted us to propose a model of division of labor that is largely based on the differential migration behavior of naiveand effector/memory-like Treg subsets [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…by use of the marker a E (CD103), into a lineage or differentiation stage of natural, naive-like a E -CD25 + Treg and into that of a E + Treg (either CD25 + or CD25 -) with the phenotype of effector/memory cells [3], a distinction that might partially relate to the differentiation into natural and adaptive Treg [4]. Whereas naive-like Treg express molecules including CD62L and CC chemokine receptor 7 (CCR7), allowing recirculation through lymphoid tissues [3,5,6], effector/memory-like Treg display a high chemokine and homing receptor versatility and efficiently migrate into peripheral tissues and inflamed sites [3,5,[7][8][9][10][11][12]. These findings prompted us to propose a model of division of labor that is largely based on the differential migration behavior of naiveand effector/memory-like Treg subsets [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Treg are by no means homogeneous, but rather can be subdivided into naïve-like subsets, which preferentially recirculate through lymphoid tissues, and effector/memory subsets, which efficiently migrate into peripheral sites and sites of ongoing immune responses [30][31][32][33]. Thus, it is not surprising that Treg display a high HR versatility [31,[34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Treg are by no means homogeneous, but rather can be subdivided into naïve-like subsets, which preferentially recirculate through lymphoid tissues, and effector/memory subsets, which efficiently migrate into peripheral sites and sites of ongoing immune responses [30][31][32][33]. Thus, it is not surprising that Treg display a high HR versatility [31,[34][35][36][37][38][39].A few studies have demonstrated the capacity of Treg to down-regulate established immune reactions [31,[40][41][42], and, therefore, it has been suggested that regulation might act locally in the inflammatory environment. Indeed, we and others have recently demonstrated that expression of certain HR such as selectin ligands and chemokine receptors on Treg subsets critically influences their suppressive capacity in vivo [43][44][45][46], suggesting that appropriate localization is indispensable for Treg function [30].…”
mentioning
confidence: 99%
“…It has been reported that CD4 ϩ CD25 ϩ or FoxP3 ϩ Tregs express CCR4, CCR5, CCR7, CCR8, CCR10, CXCR4, and CXCR5 and L-selectin, E-selectin, and P-selectin ligands (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). CD103 ϩ Tregs express effector/memory-type trafficking receptors, and CD103 Ϫ Tregs express lymphoid tissue homing receptors (20).…”
mentioning
confidence: 99%